KAJI ULANG PERENCANAAN BANGUNAN PENAHAN SEDIMEN (CHECK DAM I) DI DAERAH ALIRAN SUNGAI CILIMAN KABUPATEN LEBAK - Dinihari Mulya Lestari; Fitri Dwirani; Nanda Syuhada Syuhada (LPPM, 2019)
Check dam is a river shaped river with its completeness, which serves to control the speed, flow and direction of the sediment flow in the riverbed. Check dam I in the Ciliman River Basin Cicaringin Village, Gunung Kencana District Lebak Regency is one of the planned check dam of three locations planned by the Cidanau-Ciujung- Cidurian River Basin through Planning Consultant PT Prana Kurnia Pratama in 2010th which aims to tackling or reducing the problem of the amount of sediment transport on the Ciliman River thus preventing the siltation of the river and the reduction of river cross section. Cicaringin's check dam I condition is irrelevant at the time of the initial design that was designed with 50 minutes replanning plan (Q50) calculated by HSS Gama I method of 462,257 m3/sec, so it needs to be reviewed by analyzing the stability of check dam with using a flood discharge plan 25 years rework (Q25) of 429,108 m3/sec calculated with the same motede, with catchman area of 117.00 km2. This study was conducted to determine whether the stability of check dam I Cicaringin is safe against the forces acting with (Q25). The calculated forces are own gravity, seismic force, lifting force, water weight, water pressure and calculated dam weights analysis are hydraulic gradient, eccentricity, soil bearing capacity, bolsters and shear forces. The results show that the dimensions of chek dam are safe against shear forces, bolsters, eccentricity, soil carrying capacity and forces that work well during normal water level conditions and flood waterconditions.